Analysis Of The Effect Of Additional Employee Income (Tpp) And Work Ability On The Performance Of State Civil Apparatus (Asn) In Tanjung Mulia Village In Pasar Manna District South Bengkulu - Apta, Muhammad Ferdi; Soleh , Ahmad; Nurzam, Nurzam (Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
The purpose of this study is to determine the effect of additional employee income and work ability on the performance of ASN employees in Tanjung Mulia Village, South Bengkulu Regency. This research method uses quantitative research with a descriptive approach. Data analysis methods are validity testing, multiple linear regression, determination testing and hypothesis testing. The research sample was 20 employees in Tanjung Mulia Village, Pasar Manna District, South Bengkulu Regency.The results of the study on the SPSS test that had been carried out were as many as the questionnaires submitted to respondents were all valid, namely less than 0.05. Then the reliability test stated that 3 research variables were reliable because the alpha crownbach> 0.6 which means reliable. In the hypothesis test, it states that the TPP variable and the work ability variable <0.05, which means that the TPP and ability variables have a significant effect on employee performance in Tanjung Mulia Village, Pasar Manna District, South Bengkulu Regency